Nelayan dan Penangkapan Ikan “Nike” di Perairan Teluk Gorontalo, Teluk Tomini (Indonesia) - Nuralim Pasisingi; Abdul Hafidz Olii (Jurnal Sumberdaya Akuatik Indopasifik, 2023)
Gorontalo Bay, the estuary of the Bone River, is part of the Tomini Bay area. Nike, a school fish larva appearing in Estuary Bone only a few days monthly, suits the prima donna of the community and fishermen in Gorontalo. Any technical matters related to “nike” fishing have never been reported in a structured method. Therefore, scientific investigation is necessary to provide relevant information. This study aimed to identify the fishermen’s profiles and matters linked to “nike” fishing. Structured interviews using a questionnaire instrument were conducted to obtain information from Gorontalo fishermen who actively catch “nike” every month in Gorontalo Bay. The results showed that most “nike” Gorontalo fishermen are elementary and junior high school graduates aged 20-60. Nike fishing is done in groups using wooden boats with totalu'o or tagahu fishing gear. The operational fishing capital they used could be from boat owners, groups, or loans from fish collectors. Most fishermen sell their catch at the Fish Auction, Gorontalo City, with an average price of Rp. 20.000 to Rp. 40.000 per kg. According to fishermen, the “nike” fish population tends to be abundant in the waters during the east monsoon. When the population in the seas is high enough, the fishermen’s catch reaches more than 100 kg per trip. The high intensity of catching and the quantity of fish caught per season of emergence can threaten the sustainability of the “nike” population in nature. A more comprehensive follow-up study is needed to analyze the synergies of economic, social, and ecological aspects to increase “nike” fishermen’s welfare in Gorontalo with the sustainability of the “nike” fish guarantee.